Autophagy Machinery as a Promising Therapeutic Target in Endometrial Cancer - Nuñez-Olvera, Stephanie I.; Gallardo-Rincón, Dolores; Puente-Rivera, Jonathan; Salinas-Vera, Yarely M.; Marchat, Laurence A.; Morales-Villegas, Raúl; López-Camarillo, César (Frontiers in Oncology, 2019)
Endometrial cancer is the fourth most frequent neoplasia for women worldwide, and over the past two decades it incidence has increased. The most common histological type of endometrial cancer is endometrioid adenocarcinoma, also known as type 1 endometrial cancer. Endometrioid endometrial cancer is associated with diverse epidemiological risk factors including oestrogen use, obesity, diabetes, cigarette smoking, null parity, early menarche and late menopause. Clinical effectiveness of chemotherapy is variable, indicating that novel molecular therapies against specific cellular processes associated to cell survival and resistance to therapy, such as autophagy, urged to ameliorate the rates of success in endometrial cancer treatment. Autophagy (also known as macroautophagy) is a specialized mechanism that maintains cell homeostasis which is activated in response to cellular stressors including nutrients deprivation, amino acids starvation, hypoxia and metabolic stress to prolong cell survival via lysosomal degradation of cytoplasmic macromolecules and organelles. However, in human cancer cells, autophagy has a controversial function due to its dual role as self-protective or apoptotic. Conventional antitumor therapies including hormones, chemotherapy and ionizing radiation, may activate autophagy as a pro-survival tumor response contributing to treatment resistance. Intriguingly, if autophagy continues above reversibility of cell viability, autophagy can result in apoptosis of tumor cells. Here, we have reviewed the mechanisms of autophagy described in endometrial cancers, including the role of PI3K/AKT/mTOR, AMPK-mTOR and p53 signaling pathways that trigger or inhibit the process and thus representing potential molecular targets in therapeutic clinical approaches. In addition, we discussed the recent findings indicating that autophagy can be modulated using repurposing drugs which may leads to faster experimentation and validation, as well as more easy access of the medications to patients. Finally, the promising role of dietary compounds and microRNAs in autophagy modulation is also discussed. In conclusion, although the research about autophagy is scarce but ongoing in endometrial cancer, the actual findings highlight the promising usefulness of novel molecules for directing targeted therapies.